The Effectiveness Of The Baas Program (Father Following Stunting Children) In The Framework Of Reduce The Rate Of Stunting Incidents At Deagintungkerta, The Work Area Of Puskesmas Anggadita Klari District, Karawang District, In 2022 - Erlis Herliati; Nanik Yuliwati (The International Science of Health Journal, 2023)
Background : In order to support stunting reduction activities, the West Java BKKBN has formed a family assistance program which is carried out by a family assistance team consisting of midwives, cadres and PKK staff to eliminate the main factors causing stunting. Research purposes : To find out more in-depth information about the effectiveness of the BAAS (Foster Father of Stunting Children) program in the form of input, output and process indicators in order to reduce the incidence of stunting in Gintungkerta Village, Kari District, Karawang Regency in 2022. Types of research : The research was conducted in June 2023. The informants and key informants consisted of 16 people. This study uses in-depth interview techniques with a qualitative approach method. Research result : Input: "... me and the cadre have been running the BAAS program for 7 months, all the tools were provided from the village, all items were entered into the records (inventory)."(BD1). Process: "... my child was given food which remained to be eaten by the dede and the cadre, then told the midwife that it had to be eaten directly by the dede and could not be given to others" (IB5). Output: "... after evaluating the total assistance in implementing the BAAS program this month, the results were 21 out of 53 stunted toddlers who were declared to have graduated were not stunted anymore or it could be said that they were normal in terms of weight/height..." (BD2) Conclusion : Input: Involvement in the implementation of the BAAS program is not only BKKBN, DinKes, sub-districts and villages, but because there are many factories in the Gintungkerta Village area, there are several companies that are supporting the BAAS program for 53 people targeted for stunting toddlers. Process : The accompanying team/cadres deliver the BAAS program to the target in the form of ready-to-eat PMT that has been processed. Output: The results of the evaluation were 21 out of 53 targeted stunting toddlers who experienced a change in status from stunting to normal. Barriers and constraints : There is no program sustainability, target data is out of sync, there are no incentives for cadres.